Development impact of Non-Bank Financial Intermediaries on economic growth in Malaysia: an empirical investigation - Islam, Mohd Aminul; Osman, Jamil (Center for Promoting Ideas (CPI), 2011)
This paper aims to empirically examine the development impact of Non-Bank Financial Intermediaries on economic growth in Malaysia using time series data over the period spanning 1974 to 2004. The study employs bounds testing approach to cointegration and error correction mechanism to investigate the existence of a long run equilibrium relationship between NBFIs and economic growth. The study finds evidence of a long run cointegrating relationship between NBFIs and real per capita income. The empirical results indicate that the development of NBFIs positively and significantly influences per capita income in Malaysia. In addition, the CUSUM and CUSUMSQ tests confirm the stability of the model.